Vocal-pedagogical guidelines assisting the methods of working with mutating voices - Lyutskanova, Doroteya (Young Scientific Music and Dance Forum : Conference with international participation, 2021)
The report examines the complex relationship between vocal science and singing, the application of scientific researches and discoveries about the physiology of sound formation as a necessary part of the methodical work of the vocal pedagogue. In recent years, the demands to build a healthy voice, especially when a mutation occurs, pose a number of questions to the singing teacher. How should scientific knowledge be interpreted and practiced? How should effective learning outcomes be achieved among adolescents? How will scientific advancements in the science of voice enrich methodological tools to build and preserve the voice of adolescents? Is science needed to interfere so deeply in the art of singing and whether the students will sing better if they are aware of the physiology and anatomy of the larynx? The answer to these questions can be found in the shared experience of a number of emblematic names in vocal pedagogy, which have left many vocal books, articles and teaching aids inherited.